2020
DOI: 10.1021/acs.nanolett.0c02991
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarizability of Plasmonic Meta-Atoms in Metasurfaces

Abstract: Plasmonic metasurfaces are promising as enablers of nanoscale nonlinear optics and flat nonlinear optical components. Nonlinear optical responses of such metasurfaces are determined by the nonlinear optical properties of individual plasmonic meta-atoms. Unfortunately, no simple methods exist to determine the nonlinear optical properties (hyperpolarizabilities) of the meta-atoms hindering the design of nonlinear metasurfaces. Here, we develop the equivalent RLC circuit (resistor, inductor, capacitor) model of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 64 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…[37]. After some numerical experiments using our existing hydrodynamics solver 38 , we found that including hydrodynamic terms has very little effect on the nonlinearity when solved in conjunction with the TTM.…”
Section: Model For Tco Nonlinear Optical Responsementioning
confidence: 99%
“…[37]. After some numerical experiments using our existing hydrodynamics solver 38 , we found that including hydrodynamic terms has very little effect on the nonlinearity when solved in conjunction with the TTM.…”
Section: Model For Tco Nonlinear Optical Responsementioning
confidence: 99%
“…The highest Q -factor of these FLRs is 800 (FLR2, at a wavelength of 1550 nm), which is 2 orders of magnitude higher than those associated with the LSPRs of the individual nanoparticles and an order of magnitude higher than that of Fabry–Pérot SLR modes . With such high Q -factors and the strong optical nonlinearity of metals, the FLR metasurfaces could find applications in nonlinear processes, such as nondegenerate four-wave mixing (FWM)…”
Section: Resultsmentioning
confidence: 99%
“…These extra terms would broaden the functionality of our model by taking into account even‐ordered nonlinearities such as second‐harmonic generation. After some numerical experiments using our existing hydrodynamics solver, [ 44 ] we found that including hydrodynamic terms has very little effect on the permittivity change when solved in conjunction with the TTM. In fact the hydrodynamic terms are nonlocal, adding an unnecessary computational load, [ 45 ] and thus we chose to ignore these terms for the present work.…”
Section: Model For Tco Time‐varying Nonlinear Optical Responsementioning
confidence: 99%